Dielectric properties of novel polyurethane–PZT–graphite foam composites. (12th August 2016) - Tolvanen, Jarkko; Hannu, Jari; Nelo, Mikko; Juuti, Jari; Jantunen, Heli
Abstract: Flexible foam composite materials offer multiple benefits to future electronic applications as the rapid development of the electronics industry requires smaller, more efficient, and lighter materials to further develop foldable and wearable applications. The aims of this work were to examine the electrical properties of three- and four-phase novel foam composites in different conditions, find the optimal mixture for four-phase foam composites, and study the combined effects of lead zirconate titanate (PZT) and graphite fillers. The flexible and highly compressible foams were prepared in a room-temperature mixing process using polyurethane, PZT, and graphite components as well as their combinations, in which air acted as one phase. In three-phase foams the amount of PZT varied between 20 and 80 wt% and the amount of graphite, between 1 and 15 wt%. The four-phase foams were formed by adding 40 wt% of PZT while the amount of graphite ranged between 1 and 15 wt%. The presented results and materials could be utilized to develop new flexible and soft sensor applications by means of material technology.